Development and Application of Medicine-Engineering Integration in the Rehabilitation of Traumatic Brain Injury. - Wang, Qingyong; Sun, Weibo; Qu, Yuanyuan; Feng, Chuwen; Wang, Delong; Yin, Hongna; Li, Chaoran; Sun, Zhongren; Sun, Dongwei (BioMed Research International, 2021)
The rapid progress of the combination of medicine and engineering provides better chances for the clinical treatment and healthcare engineering. Traumatic brain injury (TBI) and its related symptoms have become a major global health problem. At present, these techniques has been widely used in the rehabilitation of TBI. In this review article, we summarizes the progress of the combination of medicine and industry in the rehabilitation of traumatic brain injury in recent years, mainly from the following aspects: artificial intelligence (AI), brain-computer interfaces (BCI), noninvasive brain stimulation (NIBS), and wearable-assisted devices. We believe the summary of this article can improve insight into the combination of medicine and industry in the rehabilitation of traumatic brain injury.